A single-dose nitrate-producing dietary supplement affects cardiorespiratory endurance and muscular fitness in healthy men: A randomized controlled pilot trial. (July 2021) - Todorovic, Nikola; Stajer, Valdemar; Ratgeber, Laszlo; Betlehem, Jozsef; Acs, Pongrac; Maksimovic, Nebojsa; Ostojic, Sergej M
Introduction: The main aim of this pilot study was to examine the effects of a single-dose intervention with a novel nitrate-producing formulation (MagNOVOx™) on biomarkers of cardiorespiratory endurance and muscular fitness in 12 healthy men. Methods: The study participants (age = 22.7 ± 2.8 years, height = 184.1 ± 5.7 cm, and weight = 82.5 ± 8.4 kg) were randomly allocated to receive either a single dose of MagNOVOx™ or a placebo (inulin) in a cross-over design. The primary outcome for this study was the change in running time to exhaustion evaluated at baseline (before supplementation) and post-intervention. Results: Time to exhaustion was improved after the intervention in 8 out of 11 participants (72.7%) who received MagNOVOx™, and in 1 out of 11 participants (9.1%) who received placebo ( p = 0.004), and MagNOVOx™ outcompeted placebo in terms of improving leg press performance ( p < 0.01). No significant differences between MagNOVOx™ and placebo were found for blood pressure responses ( p > 0.05). Conclusion: These promising findings should be further corroborated in medium- and long-term trials, and different populations, while the exact mechanism of MagNOVOx™ requires additional physiological studies.